Enhancing Community Welfare: Community Data Collection for Kwh Installation in Kandawati Village - Ahmad Rayhan; Fitria Dwi Yulianty (Probono and Community Service Journal, 2022)
This research is motivated by a community phenomenon, specifically the residents of Kandawati Village, where until now some of them still have not used Kilo Watt Hour (Kwh) or commonly called a meter to calculate electricity bills. The main reason is that some residents are constrained by the problem of initial installation costs and future usage costs. Whereas according to Government Regulation no. 26 of 2006 concerning the Provision and Utilization of Electric Power states that electricity has an important role in the development of technology and supports the welfare of the community. Therefore, to answer this issue, the author uses the method of collecting field study data or direct observation of the residents of Kandawati Village. Then from these observations, the writer then carried out documentation, namely data collection which included information, evidence and related citizen activities based on written records.